THE EFFECT OF DOLOMITE ON THE GROWTH AND PRODUCTION OF CUCUMBER (Cucumis sativus L.): PENGARUH PEMBERIAN DOLOMIT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) - Hulu, Arahman (LPPM UPMI, 2024)
Cucumber plants are a group of fruits that are in great demand in various circles, cucumbers are often used as fresh vegetables and processed as juice and stir-fry, so the demand for cucumber fruit production is very high. In 2020, cucumber production has decreased due to the low productivity of cucumber plants. To increase the production and productivity of cucumber plants requires effective plant cultivation techniques, especially in basic fertilization so as to produce maximum production. The fertilizer used in this study is agricultural lime or dolomite. This study used a non-factorial group randomized design (RAK). The treatment of dolomite (D) with 3 levels, namely D0 = 0 gr/plot, D1 = 100 gr/plot, and D2 = 200 gr/plot. The results of Anova analysis of variance for the observation parameters of plant height (cm), fruit weight (gr), and number of fruits showed no significant effect but the observation of fruit diameter (mm) had a significant effect. The best treatment average is D2 = 200 gr/plot.